American government : competition and compromise - Rockwell, Stephen J., 1966-; Woll, Peter, 1933- (Boston : McGraw-Hill, 2001)
A brief introduction to American government. The book opens by discussing the media, the place where the public see the government daily. Then it moves to looking at the more traditional topics of constitution and institutions of government.
Part One. Americans and Politics. 1. The Media. 2. Interest Groups. 3. Political Parties. 4. Elections, Campaigns, and Voting. Part Two. Competition by Design. 5. The Constitution. 6. Civil Liberties and Civil Rights. Part Three. Institutions and Governing. 7. The Bureaucracy. 8. The Presidency. 9. Congress. 10. The Judiciary.
Includes bibliographical references and index.
Keywords: Democracy -- United States; United States -- Politics and government